White Matter Hyperintensity Burden and Disability in Older Adults: Is Chronic Pain a Contributor?. Issue 6 (7th March 2013) - Buckalew, Neilly; Haut, Marc W.; Aizenstein, Howard; Rosano, Caterina; Edelman, Kathryn Dunfee; Perera, Subashan; Marrow, Lisa; Tadic, Stasa; Venkatraman, Vijay; Weiner, Debra
Abstract : Objective: To primarily explore differences in global and regional white matter hyperintensities (WMH) in older adults with self‐reported disabling and nondisabling chronic low back pain (CLBP) and to examine the association of WMH with gait speed in all participants with CLBP. To secondarily compare WMH of the participants with CLBP with the pain‐free controls. Design: A cross‐sectional, case‐control study. Setting: University of Pittsburgh. Participants: Twenty‐four community‐dwelling older adults: 8 with self‐reported disabling CLBP, 8 with nondisabling CLBP, and 8 were pain‐free. Exclusions were psychiatric or neurologic disorders (either central or peripheral), substance abuse, opioid use, or diabetes mellitus. Methods: All participants underwent structural brain magnetic resonance imaging, and all participants with CLBP underwent the 4‐m walk test. Main Outcome Measurements: All the participants were assessed for both global and regional WMH by using an automated localization and segmentation method, and gait speed of participants with CLBP. Results: The disabled group demonstrated statistically significant regional WMH in a number of left hemispheric tracts: anterior thalamic radiation ( P = .0391), lower cingulate ( P = .0336), inferior longitudinal fasciculus ( P = .0367), superior longitudinal fasciculus ( P = .0011), and the superior longitudinal fasciculus branch to the temporal lobe ( P = .0072). Also, there was a statistically significant negative association ( r s = −0.57; P = .0225) between the left lower cingulate WMH and the gait speed in all the participants with CLBP. There was a statistical difference in global WMH burden ( P = .0014) and nearly all regional tracts (both left and right hemispheres) when comparing CLBP with pain‐free participants. Conclusions: Our findings suggest that WMH is associated with, and hence, may be accelerated by chronic pain manifesting as perceived disability, given the self‐reported disabled CLBP patients had the greatest burden, and the pain free the least, and manifesting as measurable disability, given increasing WMH was associated with decreasing gait speed in all chronic pain participants.